PELAKSANAAN PROGRAM KELOMPOK USAHA BERSAMA FAKIR MISKIN (KUBE-FM) DI KECAMATAN DUHIADAA KABUPATEN POHUWATO - Sakbir Sakbir (Universitas Muhammadiyah Gorontalo, 2020)
This study aims to determine the implementation of the Poor Poor Joint Business Group program in Duhiadaa District, Pohuwato Regency. The results showed that; socialization has not been maximized because it is only done on limited forums. The target group of this program is right on target, this can be seen from the rigorous selection process in determining the distribution of aid. Stimulant assistance is considered inadequate. The suitability of the type of business and assistance is not appropriate, this is because to make a different business certainly requires a different amount of capital. Distribution of venture capital assistance is very good, namely by providing assistance in the form of goods in accordance with the type of business. Counseling business skills are minimal. Limited funds are the main factor in this problem. The assistance process did not run optimally due to lack of assistance and lack of budget to form more assistance teams